1995
DOI: 10.1148/radiology.194.3.7862960
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic invasion of the laryngeal cartilage: comparison of MR imaging and CT with histopathologic correlation.

Abstract: MR imaging is more sensitive than CT in detecting neoplastic invasion of cartilage, but the inability to differentiate between nonneoplastic inflammatory changes and tumor with MR imaging leads to overestimation of neoplastic invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 0 publications
8
137
1
7
Order By: Relevance
“…MRI scanning has become increasingly involved as a sensitive imaging modality for detecting neoplastic involvement of the thyroid cartilage, primarily because of its high negative-predictive value. However, recently has been demonstrated MRI low positive-predictive value (68-71%), due to its failure in distinguish edema and inflammation surrounding the tumor from the true cartilage invasion (174,177,178). In addition, it could overestimate cartilage invasion (186).…”
Section: ! -Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…MRI scanning has become increasingly involved as a sensitive imaging modality for detecting neoplastic involvement of the thyroid cartilage, primarily because of its high negative-predictive value. However, recently has been demonstrated MRI low positive-predictive value (68-71%), due to its failure in distinguish edema and inflammation surrounding the tumor from the true cartilage invasion (174,177,178). In addition, it could overestimate cartilage invasion (186).…”
Section: ! -Mrimentioning
confidence: 99%
“…MRI criteria for cartilage involvement by tumor are high signal on fat suppressed T2-w images and/or enhancement on post gadolinium fat suppressed T1-w images in the cartilage adjacent to the tumor, or the presence of extra-laryngeal tumor. The most recent studies describing radiological-pathological correlation demonstrated slightly improved sensitivity of 89-95% and reduced specificity of 74-84% relative to CAT; but accuracy still demonstrates value of about 80% as CAT (177,178,184,185). Moreover, MRI can be a lengthy and expensive procedure.…”
Section: ! -Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…CT is the most specific of the two modalities (88 Á/94%), but has a lower sensitivity (64Á/66%) [25,26] which can result in understaging. MRI has a higher sensitivity (89Á/95%), but is less specific (76 Á/84%) [26,27] which leads to overstaging. T4 tumors should therefore not be excluded from RT purely on the basis of the T4 classification.…”
Section: Discussionmentioning
confidence: 99%
“…It does not require exposure to ionizing radiation and it provides superior soft tissue contrast compared to CT. Furthermore, MRI is considered to be superior for detection of cartilage invasion 6. Also, MRI allows a multiparameter analysis (T1 weighted, T2 weighted, diffusion weighted imaging (DWI) and post‐contrast acquisition).…”
Section: Introductionmentioning
confidence: 99%